(untitled) (Prilozi za orijentalnu filologiju, 2017)
In the present paper the author explains the meaning of the literary term Muslim Oriental-like literature, used to denote Muslim literature in Oriental languages which was created by Slavonic Muslims from the Pashalik of Bosnia, who took as a model the works of Turkish, Persian and Arabic writers. In that sense, the author proposes first of all comparative studiing of the works belonging to this specific OrientaIlike litarature with its models, that will discover the .similarities as well as the differences. Apart from that, he also emphasizes the need of comparison this literature with Bosnian Muslim Aljamiado-Iiterature written in Serbo-Croatian language, and the comparison with the works belonging to other Yugoslav literatures. In that sense the author cites some initial examples.